Disentangling dissociative and nondissociative reaction dynamics in molecular mutual neutralization reactions between CO + and O − - Mathias Poline; Arnaud Dochain; Stefan Rosén; MingChao Ji; Peter Reinhed; Ansgar Simonsson; Henrik Cederquist; Henning Zettergren; Henning T. Schmidt; Mats Larsson; Shaun G. Ard; Nicholas S. Shuman; et al. (Proceedings of the National Academy of Sciences, 2026)
We have studied the mutual neutralization reaction of CO + with O − at a collision energy of ≤0.1 eV under single-collision conditions. We observe both fully dissociative (31.5 ± 1.8 %) and nondissociative (68.5 ± 1.8 %) charge transfer, involving at least five different electronically excited states in CO. From product momentum analysis, we find that the dynamics are governed by electron transfer processes at large O − -CO + separations and the competition between predissociation and radiative decay in CO Rydberg states. In the case of nondissociative charge transfer, for one of the reaction channels we observe strong vibrational excitation (4 ≤ v ≤ 8) in the product CO molecule. These data are expected to be useful for modeling astrophysical and planetary atmospheric environments where CO + and O − are present.